THE STRUGGLE OF CAPITALISM HEGEMONY IN INDONESIA (TAN MALAKA'S POLITICAL ECONOMY THOUGHT): PERGUMULAN HEGEMONI KAPITALISME DI INDONESIA (PEMIKIRAN POLITIK EKONOMI TAN MALAKA) - Ichwan Ahnaz Alamudi (KASBANA, 2024)
This research is motivated by Tan Malaka's political economy known by separate terms, namely communism-style politics and socialism-style economics. The concept of both is a resistance to the hegemony of capitalism in Indonesia, which in historical review is considered to have begun to transform into global capitalism after the industrial revolution. This research uses library data with a historical and biographical approach. This paper finds and produces that Tan Malaka wants 100% independence in this republic through the path of social revolution by means of resistance and mass movements. Mass action towards social revolution is the last way to achieve 100% independence in this case against the hegemony of imperialism, colonialism and capitalism. Socialism is here to free this nation from foreign shadows by erasing social classes so that there will be no more oppression, slavery, and exploitation of capital. Keywords: Hegemony, Socialism, Capitalism, Resistance.